The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1061/(asce)me.1943-5479.0000734
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach to Satisfying Stakeholders in Megaprojects: Balancing Mutual Values

Abstract: Stakeholder satisfaction in megaprojects has always been a critical concern in research and practice due to the dynamism, complexity, and uncertainty of the various relationships between the project and the stakeholder community. The most successful outcome for a megaproject would be achieved when it creates values fairly for stakeholder community to satisfy them. Therefore, due to the resource constraints, megaproject should create values for stakeholders proportional to the values that they put into it. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 95 publications
0
20
0
Order By: Relevance
“…Several authors define value as the relationship between the satisfaction of needs and the use of required resources [21,22] or as a balance between giving and receiving [23]. Other authors understand value as cost and prices or associate it with monetary terms [10,24].…”
Section: Generation and Loss Of Valuementioning
confidence: 99%
“…Several authors define value as the relationship between the satisfaction of needs and the use of required resources [21,22] or as a balance between giving and receiving [23]. Other authors understand value as cost and prices or associate it with monetary terms [10,24].…”
Section: Generation and Loss Of Valuementioning
confidence: 99%
“…Additionally, most stakeholders often have different motives and interests, which has emerged as a complexity concern in a megaproject. For example, the challenge discussed by Wu, Jia and Zhang (2019) has been evident for the infrastructure trunk line between the Beijing and Shenyang megaproject in China, the Mashhad Urban Railway project in Iran (Bahadorestani, Karlsen & Farimani, 2020), the partnership alliance contract between the client and contractor in Main Roads Western Australia (Galvin, Tywoniak, & Sutherland, 2021), and in some large projects around the world as examined by Di Maddaloni and Davis (2017). In this study, these aspects were categorized as social complexity, in line with the term from the context of social dimension project complexity (Maylor & Turner, 2017).…”
Section: Complexity and Megaprojectmentioning
confidence: 99%
“…Rather than examining the value or the strength of the relationship between condition variables on the outcome/result, the configurational form or the combination of variables is analyzed. Following the given objectives, the "outcome" of this study is megaproject performance, namely, the short-term success targets (e.g., the iron triangle of time, cost, and quality) (Flyvbjerg, 2014) and long-term targets (e.g., client or customer satisfaction, team satisfaction, and community benefits) (Bahadorestani et al, 2020;Sato & Chagas Jr., 2014). These outcomes are analyzed in both high and low performance.…”
Section: Research Approachmentioning
confidence: 99%
“…It can avoid the impalpable and arbitrary result. Therefore, the analysis showed that the identified papers could be categorized into five clusters: megaproject management in general [29,[116][117][118][119], megaproject sustainability [27,34,[120][121][122][123], megaproject governance [22,[124][125][126][127][128][129], megaproject investment and finance [44,48,92,[130][131][132], and megaproject risk management [95,112,[133][134][135][136]. When the topic of a paper was related to multiple clusters, the paper was classified into the most closely related cluster.…”
Section: Research Topics Of the Identified Papers In Megaproject Management Researchmentioning
confidence: 99%